Effect of ionic strength on secondary structure of velvet worm slime - Sim, Bryan Gek Hao (Nanyang Technological University, 2023)
Velvet worms are invertabates that eject a sticky slime to capture prey and for self-defence. This slime is a natural material that possesses exceptional adhesive properties, which have drawn interest for various biomedical and technological applications. Studies have been done to further understand the proteins within the slime which allows the slime to undergo liquid-to-solid transition and the adhesive properties. However not much is known about the role of the secondary structure of the slime and how in particularly the effect ionic strength has on the secondary structure. In this study, a specific sequence, herein referred as C4 has been chosen from the large molecular weight slime protein to obtain further knowledge on this topic. In this work, analytical techniques specifically circular dichroism will be utilized to analyze the secondary structure of C4 in different conditions. The results from this study could provide insights towards the formation of slime protein structure as a whole and offer progress towards creating a sustainable natural biopolymer.